Fields, sherds and scholars : recording and interpreting survey ceramics - Meens, Anna; Nazou, Margarita; Put, W. D. J. van de (Publications of the Netherlands Institute at Athens, 2023)
This book is a significant contribution to the field of survey pottery studies, which is not frequently theorised, and could also serve as a guide and provide inspiration to archaeologists designing their own survey projects and methodologies.Landscape archaeology has heavily relied on pedestrian survey as a field method for more than half a century. In most field projects, archaeological ceramics constitute the lion's share among the finds and the amount of c.